Studi Pemanfaatan Tepung Jagung, Tepung Mocaf Dan Daun Binahong Dalam Pembuatan Sweet Bread - Kurnianingsih kurnianingsih; Lia Fitriana (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2021)
Bread has many types, one of which is sweet bread, the main ingredient in processed sweet bread is wheat flour. The high use of wheat flour causes the number of wheat imports in Indonesia to be high. The decrease in wheat imports can be reduced by using local food ingredients such as corn flour, mocaf flour, and binahong leaf jam. This study aims to determine (1) the process of making gluten-free sweet bread from corn flour, mocaf flour, and binahong leaves. (2) Gluten-free sweet bread recipe from corn flour, mocaf flour, and binahong leaves (3) The level of public preference for gluten free sweet bread products from corn flour, mocaf flour, and binahong leaves. The method used in this study is the method of literature, experiments, documentation, and sensory testing. The percentage of using cornflour and mocaf flour in making glute- free sweet bread is 50%:50%, 70%:30%, and 80%:20%, of the weight of wheat flour. The results showed that gluten-free sweet bread products were the most preferred with a ratio of 70% cornflour and 30% mocaf flour.